Conversations about sculpture - Serra, Richard; Foster, Hall. (New Haven ; London : Yale University Press, 2018)
"Drawn from talks between celebrated artist Richard Serra (b. 1938) and acclaimed art historian Hal Foster held over a fifteen-year period, this volume offers revelations into Serra's prolific six-decade career and the ideas that have informed his working practice. Conversations about Sculpture is both an intimate look at Serra's life and work, with candid reflections on personal moments of discovery, and a provocative examination of sculptural form from antiquity to today. Serra and Foster explore such subjects as the artist's work in steel mills as a young man; the impact of music, dance, and architecture on his art; the importance of materiality and site specificity to his aesthetic; the controversies and contradictions his work has faced; and his belief in sculpture as experience. They also discuss sources of inspiration-from Donatello and Brancusi to Japanese gardens and Machu Picchu-revealing a history of sculpture across time and culture through the eyes of one of the medium's most brilliant figures. Introduced with an insightful preface by Foster, this probing dialogue is beautifully illustrated with duotone images that bring to life both Serra's work and his key commitments."--Cover flap.
Includes bibliographical references and index.
Keywords: Serra, Richard, -- 1938- -- Interviews